PENGARUH KOMUNIKASI ORGANISASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PT. ADHI KARYA (PERSERO) TBK. DIVISI KONSTRUKSI VI PROYEK PEMBENAHAN INTERIOR BANDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Samade, Syamsuddin; Taba, Muhammad Idrus (Universitas Kuningan, 2018)
This research aims to determine the effect of organizational communication and work environment partially and simultaneously on employee motivation at PT. Adhi Karya (Persero) Tbk. Construction Division VI Project Revamping of International Airport Interior Sultan Hasanuddin Makassar. Sample in this research amounted to 51 respondents. The data used is primary data in the from of questionnaires and interviews on a field and secondary data in the form of documentation company. The analysis method used is linear regression analysis with F test and T test. The results of the statistical test of organitational communication and work environment as a whole (simultaneous-F test) has a positive effect on employee motivation at PT. Adhi Karya (Persero) Tbk. Construction Division VI Project Revamping of International Airport Interior Sultan Hasanuddin Makassar. The results of R test show that the effect of Organizational Communication and Work Environment on Employee Motivation at PT. Adhi Karya (Persero) Tbk. Construction Division VI Project Revamping of International Airport Interior Sultan Hasanuddin Makassar is 41,6%. Based on T test, organizational communication variables have significant impact on employee motivation at PT. Adhi Karya (Persero) Tbk. Construction Division VI Project Revamping of International Airport Interior Sultan Hasanuddin Makassar. While work environment variable does not give significant impact on employee motivation at PT. Adhi Karya (Persero) Tbk. Construction Division VI Project Revamping of International Airport Interior Sultan Hasanuddin Makassar. Â Keywords : Organizational Communication, Work Environment, Employee Motivation